2023
DOI: 10.16899/jcm.1290485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Supine Position and Traction Table in the Surgical Treatment of Unstable Intertrochanteric Fractures with PFNA

Abstract: Aim: Intertrochanteric femur fractures (IFF) are a major cause of morbidity and mortality in the elderly population. Proximal femoral nail-anti-rotation (PFNA) is one of the most preferred surgical treatment methods. This study aimed to compare the clinical and radiologic results of two different patient positions used during PFNA and to reveal the intraoperative advantages and disadvantages. Material and Method: Cases operated due to IFF between January 2020 and December 2022 were retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, not only was reduction quality similar to that of the other groups, but also, when the cut-out rates were examined, it was seen that there was no significant difference from the other groups. In a study comparing the supine hemilithotomy position with the traction table, it was observed that there was no significant clinical or radiological difference between these two positions, except for duration of surgery [26] . When we look at the literature, well-leg compartment syndrome can be seen in patients in the supine hemilithotomy position, and it is thought that this complication may be due to a surgery duration of over four hours, body mass index, coagulopathy, and perioperative hypotension [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, not only was reduction quality similar to that of the other groups, but also, when the cut-out rates were examined, it was seen that there was no significant difference from the other groups. In a study comparing the supine hemilithotomy position with the traction table, it was observed that there was no significant clinical or radiological difference between these two positions, except for duration of surgery [26] . When we look at the literature, well-leg compartment syndrome can be seen in patients in the supine hemilithotomy position, and it is thought that this complication may be due to a surgery duration of over four hours, body mass index, coagulopathy, and perioperative hypotension [27,28].…”
Section: Discussionmentioning
confidence: 99%